Formulation and evaluation of gastro-retentive Tinidazole loaded floating microsphere for sustained release. (2023) - Kumar, Arun; Chanda, Silpi; Agarwal, Shriya; Singh, Manisha; Sharma, Saurabh; Vasant Bonde, Gunjan; Kumar Tiwari, Raj
Abstract: The majority of formulations available so far are used in oral forms despite of several pharmaceutical challenges, as this route is the most convenient way of drug delivery. Equally, it necessitates the required need of dose optimization for reduced toxic effects and dosing frequency. Therefore, in this study, we have conceptualized the fabrication of gastro-retentive microspheres of Tinidazole by using a variable drug and ethyl cellulose ratios that will enhance its gastric absorption, retention time along with the sustained pharmacological activity. The scanning electron microscopy and micrometrical studies exhibited their smooth, spherical surface with the particle size range of 244–294 µm. Further, they were floated successfully on the fluid due to their low bulk density and provided the sustained release in simulated gastric fluid, suggesting their suitable gastro-retentive behavior in-vivo . Thus, the prepared formulation proved to be a better gastro-retentive drug delivery system with sustained release, thereby reducing dosing frequency and side effects.